The Concept of Peace in Islam and Its Relevance to International Relations - Rizki Dian nursita; Ahmad Sahide (Graduate Program of Pontianak Institute of Islamic Studies, 2019)
Islam is often described as a religion that emphasizes the use of violence in its da'wah method. The stereotype is formed by a number of literature and media that depicted Islam as a religion of violence. This paper aims to analyze the causes of stereotype against Islam, and provides an overview of the concept of peace in Islamic perspective, and seek the relevance of the concept of peace in Islam to the study of conflict and peace in international relations. Through some literature research, the author finds that the stereotype is caused by the gap in the discourse on war and peace in Islam, thus the discourse related to the peace in Islam needs to be buzzed. Unlike the two mainstreams in International Relation Studies (Realism and Idealism), al-Quran, as the primary source of Islamic teaching, describes that a human is basically both keen to cooperate and prone to conflict, and favoring to managing the conflict through peaceful settlement. Three terms-as-silmu, as-shulhu, and al-amanu are used to conceptualize the three levels of peace in the Quranic perspective.